Il tema della conformità con la Volontà divina nel periodo moderno. Una nuova generazione di moralisti nel XVIº secolo. L’influsso dell’ockhamismo e nuove proposte per la teologia morale - Mestre, Alberto (Alpha Omega, 2016)
Summary: In this article one is brought through the thought of the moral theologians from the 16th century to St. Alphonsus Liguori, an illustrious representative of the 18th century. During these three centuries the Manualistic School was very much present with its interests and its particular structure having been well defined in the Council of Trent. The Manualistic School put forward an understanding of moral theology in such a way that reduced the scope of moral issues, leading to various shortcomings. One of these was the moving of certain moral issues previously dealt with in moral theology, strictly to the realm of spiritual or pastoral theology. A concrete example of this moving of moral issues to another realm of theology was the conformity of the human will with the Will of God. This theme no longer appeared in the manuals of moral theology as it was a topic that evaded the perspective of the Manualistic School, which was, instead, a growing and demanding vision of moral obligation, leading to moral legalism. Key words: Manualistic School, legalism, conformity, God's Will, the Will of the Father, obedience.